Pythagorean fuzzy Artinian and Noetherian ring - Meryem Fakhraoui; Idris Bakhadach; Sofyane Achik; Hamid Sadiki (Computational Algorithms and Numerical Dimensions)
The Pythagorean fuzzy set is acknowledged for its proficiency in managing uncertainty across multifarious domains. In this investigation, we advance the Pythagorean fuzzy Artinian ring as an evolutionary progression from the conventional fuzzy ring, providing a comprehensive explication of its fundamental traits. Furthermore, this study introduces Pythagorean fuzzy Noetherian rings, delineating their intrinsic attributes, thereby enriching the comprehensive comprehension of these algebraic constructs.